2015
DOI: 10.3329/bjz.v41i1.23292
|View full text |Cite
|
Sign up to set email alerts
|

Effect of freezing period on the microbial and nutrient quality of pool barb, Puntius sophore from Dhaka city retail market, Bangladesh

Abstract: Abstract:The microbiological and nutrient quality of pool barb (Jatpunti), Puntius sophore collected from three local markets -Ananda bazaar, New Market and Polashi bazaar of Dhaka, Bangladesh were assessed. The investigation confirmed more or less higher microbial load in Ananda bazaar samples than the others. The microbial quality varied with market sources as total bacterial counts (TBC), total coliform counts (TCC) and faecal coliform counts (FCC) occurred in all storage period and that crossed the accepta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…APC acceptability, according to the permissible limit recommended by [41], is not more than 5 × 10 7 CFU/g for chilled and frozen fish. The results illustrated in this study for the untreated fish were within and above the permissible limit, at nearly the same range as previous reports [48,49], and higher than other studies [50,51]. The high count of S. aureus and high percentages of isolation among different examined fish samples in this and other studies [52,53] were due to fish contamination during harvesting and subsequent unhygienic practices during handling and processing, as S. aureus does not normally appear as a part of the natural microflora of newly caught marine and cultivated fish.…”
Section: Discussionsupporting
confidence: 90%
“…APC acceptability, according to the permissible limit recommended by [41], is not more than 5 × 10 7 CFU/g for chilled and frozen fish. The results illustrated in this study for the untreated fish were within and above the permissible limit, at nearly the same range as previous reports [48,49], and higher than other studies [50,51]. The high count of S. aureus and high percentages of isolation among different examined fish samples in this and other studies [52,53] were due to fish contamination during harvesting and subsequent unhygienic practices during handling and processing, as S. aureus does not normally appear as a part of the natural microflora of newly caught marine and cultivated fish.…”
Section: Discussionsupporting
confidence: 90%
“…Ahmed et al, [23] recorded the nutrient composition of indigenous and exotic fishes fat values of P. sophore, P. ticto and X. cancila are 2.28%, 3.56% and 2.76%. Mustafa et al, [24] observed 5.59±0.88%, 5.88±0.92%, 5.65±0.95% fat values in P. sophore from different stations in Bangladesh. Nahid et al, [33] stated that the fat value in muscle of X. cancila is 4.66%.…”
Section: Fatmentioning
confidence: 93%
“…Ahmed et al, [23] reported that the nutrient composition of selected fishes and the protein values from 15.6 to 18.5%. Mustafa et al, [24] recorded 17.86 to 18.5±0.92% protein values in muscle of P. sophore. The protein content shows a strong correlation with spawning and breeding.…”
Section: Proteinmentioning
confidence: 94%
“…The nutrient composition of selected food fishes and their protein and fat values studied by Ahmed et al, [20]. Mustafa et al, [21] observed protein content in muscle of P.sophore and he stated that protein showed a correlate with spawning period. Banik and Saha, [22] explained a sharp decline in the weight of the gonad after spawning.…”
Section: Total Proteinmentioning
confidence: 99%